Menopause-associated risk of cardiovascular disease - Anagnostis, Panagiotis; Lambrinoudaki, Irene; Stevenson, John C; Goulis, Dimitrios G (Endocrine Connections, 2022)
Cardiovascular disease (CVD) is of major concern in women entering menopause. The changing hormonal milieu predisposes them to increased CVD risk, due to a constellation of risk factors, such as visceral obesity, atherogenic dyslipidemia, dysregulation in glucose homeostasis, non-alcoholic fatty liver disease and arterial hypertension. However, an independent association of menopause per se with increased risk of CVD events has only been proven for early menopause (<45 years). Menopausal hormone therapy (MHT) ameliorates most of the CVD risk factors mentioned above. Transdermal estrogens are the preferable regimen, since they do not increase triglyceride concentrations and they are not associated with increased risk of venous thromboembolic events (VTE). Although administration of MHT should be considered on an individual basis, MHT may reduce CVD morbidity and mortality, if commenced during the early postmenopausal period (<60 years or within ten years since the last menstrual period). In women with premature ovarian insufficiency (POI), MHT should be administered at least until the average age of menopause (50–52 years). MHT is contraindicated in women with a history of VTE and is not currently recommended for the sole purpose of CVD prevention. The risk of breast cancer associated with MHT is generally low and is mainly conferred by the progestogen. Micronized progesterone and dydrogesterone are associated with lower risk compared to other progestogens.